Influence of parents on obesity in adolescents. - Ng, Trina Xue Min. (2012)
With the rise of the obesity pandemic, obesity has become a serious health issue worldwide. The literature has focused much on the influence of parents on children’s obesity. However, there is little research examining parental influence on obesity in adolescents. Furthermore, parents do continue to have an influence during the adolescence stage. Adolescence is a critical stage for obesity. There is an observed marked decrease in physical activities and the risks of psychosocial morbidity further exemplifies the need to pay greater attention to adolescents. Hence, this paper aims to consolidate this evidence. Parents have been found to influence obesity through hereditary modes, parents’ own activity level, the level of social support available, parenting style, parents’ views and attitudes on exercising and food choices, economic conditions and through the promotion of habits. This has implications in guiding intervention works which enlists parents’ assistance in reducing obesity rates as well as examining other less explored research areas in obesity.